2021
DOI: 10.3389/fnana.2021.763298
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Afferent Inputs to the Caudate Nucleus, Putamen, and Accumbens Nucleus in the Tree Shrew Striatum

Abstract: Day-active tree shrews have a well-developed internal capsule (ic) that clearly separates the caudate nucleus (Cd) and putamen (Pu). The striatum consists of the Cd, ic, Pu, and accumbens nucleus (Acb). Here, we characterized the cytoarchitecture of the striatum and the whole-brain inputs to the Cd, Pu, and Acb in tree shrews by using immunohistochemistry and the retrograde tracer Fluoro-Gold (FG). Our data show the distribution patterns of parvalbumin (PV), nitric oxide synthase (NOS), calretinin (CR), and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 140 publications
(154 reference statements)
2
2
0
Order By: Relevance
“…In contrast, many well-defined and TH-positive dopaminergic neurons were present in the healthy side of the substantia nigra. The somas of these neurons were mostly spindle-shaped, with clearly visible brown-stained processes and blue-centered nuclei (Figure 7E), similar to the recently published study on midbrain anatomy and cellular morphology in normal tree shrews (Ni et al, 2021).…”
Section: Tree Shrews Exhibited Marked Nigral Dopaminergic Neuronal Lo...supporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, many well-defined and TH-positive dopaminergic neurons were present in the healthy side of the substantia nigra. The somas of these neurons were mostly spindle-shaped, with clearly visible brown-stained processes and blue-centered nuclei (Figure 7E), similar to the recently published study on midbrain anatomy and cellular morphology in normal tree shrews (Ni et al, 2021).…”
Section: Tree Shrews Exhibited Marked Nigral Dopaminergic Neuronal Lo...supporting
confidence: 89%
“…The copyright holder for this preprint this version posted September 5, 2023. ; https://doi.org/10.1101/2023.09.01.555918 doi: bioRxiv preprint (Figure 7E), similar to the recently published study on midbrain anatomy and cellular morphology in normal tree shrews (Ni et al, 2021).…”
Section: Tree Shrews Exhibited Marked Nigral Dopaminergic Neuronal Lo...supporting
confidence: 86%
“…KEGG pathways showed that the differentially upregulated genes in Pu are related to the cAMP signaling pathway, including genes such as ADCY8 (GPCR), CRHR1, GRIA3, GRIN3A, PDE4B, PLCE1, and RYR2. Thus, these data suggest that there is an overexpression of AMPA and NMDA receptor subunits (related to Ca2+ and Na+ flux) in Pu compared to CN via cAMP/GPCRs activation, which could lead to enhanced long-term potentiation and higher synaptic plasticity in Pu vs. CN and explain why CN and Pu inputs and functionalities are not equivalent 31 .…”
Section: Interneuron Populations Exhibit Region-based Differences Wit...mentioning
confidence: 89%
“…KEGG pathways showed that the differentially upregulated genes in Pu are related to the cAMP signaling pathway, including genes such as ADCY8 (GPCR), CRHR1, GRIA3, GRIN3A, PDE4B, PLCE1, and RYR2. Thus, these data suggest that there is an over-expression of AMPA and NMDA receptor subunits (related to Ca2 + and Na + ux) in Pu compared to CN via cAMP/GPCRs activation, which could lead to enhanced long-term potentiation and higher synaptic plasticity in Pu vs. CN and explain why CN and Pu inputs and functionalities are not equivalent 31 .…”
Section: Validation Of Interneuron Taxonomy With Uorescent In Situ Hy...mentioning
confidence: 87%